The Relationship Among Consumption, Income, Stock Wealth and Housing Weatlh: Evidence from Canada - Jiang, Shan (Université d'Ottawa | University of Ottawa, 2004)
This paper uses data from Statistics Canada to examine the relationship among disposable income, housing wealth , stock market wealth and consumption . Estimation is based on a vector error correction model, which investigates not only the dynamic respons